Pregnant Agencies: Movement and Participation in Maternal–Fetal Interactions - Quintero, Alejandra Martínez; De Jaegher, Hanne (Frontiers in Psychology, 2020)
Pregnancy presents some interesting challenges for the philosophy of embodied cognition. Mother and fetus are generally considered to be rather passive during pregnancy, both individually and in their relation. In this paper, we use the enactive operational concepts of autonomy, agency, individuation, and participation to examine the relation between mother and fetus in utero. Based on biological, physiological, and phenomenological research, we explore the emergence of agentive capacities in embryo and fetus, as well as how the pregnant person’s bodily experience and bodily movement transforms as pregnancy advances. We show that qualitatively different kinds of agency have their beginnings already in utero, and to what extent fetal and maternal movement modulates affectivity and individuation in pregnancy. We thus propose that mother and fetus are both agents who participate in pregnancy. Pregnancy then emerges as a relational developmental organisation that anchors and holds its developing participants. We end the paper with reflections on ethical implications of this proposal, and suggestions for future research.